2011
DOI: 10.1089/end.2010.0406
|View full text |Cite
|
Sign up to set email alerts
|

Hernia Repair During Endoscopic Extraperitoneal Radical Prostatectomy: Outcome After 93 Cases

Abstract: EERPE combined with either a unilateral or bilateral laparoscopic hernia repair appears to be a safe and effective procedure. The incidence of complications related to either EERPE or the hernia repair was not increased. Oncological and functional outcome of EERPE seems not to be influenced by the performance of inguinal hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Herniorrhaphy, onlay mesh totally extraperitoneal or transabdominal preperitoneal Celik, 27 S anchez-Ortiz, 13 Do, 28 Kyle, 29 Teber, 30 Rogers, 31 Nakamura 32 et al Herniorrhaphy mesh or mesh plug Joshi, 33…”
Section: Preoperativementioning
confidence: 99%
“…Herniorrhaphy, onlay mesh totally extraperitoneal or transabdominal preperitoneal Celik, 27 S anchez-Ortiz, 13 Do, 28 Kyle, 29 Teber, 30 Rogers, 31 Nakamura 32 et al Herniorrhaphy mesh or mesh plug Joshi, 33…”
Section: Preoperativementioning
confidence: 99%
“…Second, regarding the incidence of complications related to either TEP or ELRP, an infected prosthetic graft could have serious complications, though the performance of TEP alone has a very low incidence of infection. According to previous reports, 7,8 the incidence of complications related to ELRP, such as infections, symptomatic lymphoceles and bladder neck stenosis, does not seem to be influenced by TEP repair. The present patient did not have infected urine before surgery.…”
Section: Discussionmentioning
confidence: 83%
“…Either the transperitoneal or extraperitoneal approach is feasible. In recent studies, many investigators showed the similar conclusion [25,37,50]. Although, the laparoscopic totally extraperitoneal after radical prostatectomy could be influenced by surgeons, skill and experience recommended by J.-L. et al [51].…”
Section: Prophylactic Proceduresmentioning
confidence: 87%
“…The overall incidence of inguinal hernia was 8.3% (41 of 493 patients). Minh Do, M. D. [25] performed 93 patients with endoscopic extraperitoneal radical prostatectomy (EERPE) and observed no hernia recurrence during the follow-up period. Jungle Chi-Hsiang Wu and Johan Stranne et al [26][27][28] suggested a lower incidence of postoperative IH after robot-assisted laparoscopic radical prostatectomy (RALP).…”
Section: Incidencementioning
confidence: 99%